Study guide for Memmler's structure and function of the human body - Hull, Kerry L.; Cohen, Barbara Jansobn (Wolters Kluwer, 2020)
Maximize your study time, improve your performance on exams, and succeed in your course and beyond with this companion Study Guide for Memmler's Structure and Function of the Human Body, 12th Edition. Filled with empowering self-study tools and learning activities for every learning style, this practical Study Guide follows the organization of the main text chapter by chapter, helping you every step of the way toward content mastery. Chapter overviews highlight the most important chapter concepts at a glance. Writing exercises hone your clinical communication skills. Coloring and labeling exercises test your understanding of anatomic structures. Concept maps reinforce connections between common A&P concepts. Practical application scenarios challenge you to translate basic concepts to practice settings. Matching exercises test your knowledge of anatomic relationships. Short-essay questions encourage critical thinking. Multiple-choice, fill-in-the-blank, and true-false questions test retention of key textbook content. Information on real-life anatomy and physiology in action and updates on current research trials and applications keeps you current with the latest clinical practices.